The association between food addiction, disordered eating behaviors and food intake - Sengor, Gulhan; Gezer, Ceren (Pontificia Universidade Catolica Campinas, 2020)
Objective This study was conducted with 370 undergraduate students to investigate the relationship between food intake, food addiction and disordered eating behavior. Methods The Yale Food Addiction Scale, Eating Attitude Test-26 and Food Frequency Questionnaire were used to assess food addiction, disordered eating behavior and food intake. Results A positive weak correlation was found between the Yale Food Addiction Scale and daily energy, carbohydrate and fat intake (r=0.228, p<0.001; r=0.222, p<0.001; r=0.225, p<0.001 respectively) whereas a negative weak correlation was found between Eating Attitude Test-26 and daily energy and carbohydrate intake (r=-0.105, p=0.044; r=-0.116, p=0.025 respectively). Conclusion Food intake is associated with food addiction and disordered eating behaviour. Further research should be conducted with a larger population also examining body composition, exercises and financial situation of the individuals because all of these factors have an influence on the nutritional status and eating behavior as well.
Keywords: Feeding and eating disorders; Food addiction; Food consumption